2013
DOI: 10.1016/j.watres.2012.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of an integrated electrodisinfection/electrocoagulation process with Al bipolar electrodes for urban wastewater reclamation

Abstract: In this work, a novel integrated electrochemical process for urban wastewater regeneration is described. The electrochemical cell consists in a Boron Doped Diamond (BDD) or a Dimensionally Stable Anode (DSA) as anode, a Stainless Steel (SS) as cathode and a perforated aluminum plate, which behaves as bipolar electrode, between anode and cathode. Thus, in this cell, it is possible to carry out, at the same time, two different electrochemical processes: electrodisinfection (ED) and electrocoagulation (EC). The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 34 publications
1
63
0
1
Order By: Relevance
“…The mineral composition of the biomass was measured by using an inductively coupled plasma spectrometer (model Liberty Sequential, Varian) according to the procedure described by Cotillas et al [14] (plasma emission spectroscopy). In order to evaluate the total metal concentration, microalgae biomass samples were diluted to 50:50 v/v using 4N HNO 3 in order to ensure the total solubility of the metal.…”
Section: Biomass Samples Characterizationmentioning
confidence: 99%
“…The mineral composition of the biomass was measured by using an inductively coupled plasma spectrometer (model Liberty Sequential, Varian) according to the procedure described by Cotillas et al [14] (plasma emission spectroscopy). In order to evaluate the total metal concentration, microalgae biomass samples were diluted to 50:50 v/v using 4N HNO 3 in order to ensure the total solubility of the metal.…”
Section: Biomass Samples Characterizationmentioning
confidence: 99%
“…This may be due to the fact that, at appropriate j values, sufficient coagulants are generated via anodic dissolution and they interact with OH ions to form respective precipitates (eqs 1−4) to remove impurities by adsorption and flotation (precipitation) mechanisms. 30 Figure S2a,b (Supporting Information). After 150 min of electrolysis, 68.4% TOC removal and 98.5% turbidity removal were observed at optimum j with the SS−SS electrode combination.…”
Section: Resultsmentioning
confidence: 99%
“…Coupling EO technology with some other advanced water treatment technique improved the disinfection results [147][148][149][150][151][152]. Sonoelectrocatalytic disinfection using TiO 2 as electrode effectively inactivated E. coli bacteria [147].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Cotillas et al [150] optimized an integrated electrodisinfection/electrocoagulation process for urban wastewater reclamation. Results showed that the performance of the process strongly depended on the characteristics of the initial effluent and cell configuration cathode (inlet)-anode (outlet).…”
Section: Accepted Manuscriptmentioning
confidence: 99%